Risk and Return in Fixed-Income Arbitrage: Nickels in Front of a Steamroller? - Duarte, Jefferson; Longstaff, Francis A.; Yu, Fan (Review of Financial Studies, 2007)
[We conduct an analysis of the risk and return characteristics of a number of widely used fixed-income arbitrage strategies. We find that the strategies requiring more "intellectual capital" to implement tend to produce significant alphas after controlling for bond and equity market risk factors. These positive alphas remain significant even after taking into account typical hedge fund fees. In contrast with other hedge fund strategies, many of the fixed-income arbitrage strategies produce positively skewed returns. These results suggest that there may be more economic substance to fixedincome arbitrage than simply "picking up nickels in front of a steamroller."]